1466Vitamin D status before, during and after treatment and ovarian cancer survival. (2nd September 2021) - Ross, Tanya; Webb, Penny; Neale, Rachel
Abstract: Background: Previous work found higher serum 25-hydroxyvitamin D (25(OH)D) [circulating form of vitamin D] concentrations at diagnosis were associated with longer survival in patients with ovarian cancer (OvCa). There was no evidence for an association with 25(OH)D after primary treatment, but power was limited. Our aim was to reassess this association in a larger sample, including measures collected during treatment and using techniques to deseasonalise 25(OH)D. Methods: Participants were diagnosed between 2002-2006 and 2012-2015 from the Australian Ovarian Cancer Study (AOCS) and the Ovarian Cancer, Prognosis and Lifestyle (OPAL) study, respectively. 25(OH)D concentrations were available for 676 at diagnosis (AOCS), 805 during treatment (AOCS:208; OPAL:597) and 861 after completion of primary treatment and before recurrence (AOCS:342; OPAL:519); 1006 AOCS samples were included in the previous analysis. Sociodemographic, diet and lifestyle data came from questionnaires self-completed at recruitment, and clinical/survival data from medical records, supplemented with National Death Index linkage. We will use Cox regression and non-parametric models to examine associations with survival. Results: Median 25(OH)D concentrations were lowest during treatment, intermediate at diagnosis and highest after treatment (AOCS 51, 64, and 71 nmol/L, respectively). 5-year survival was 50% in AOCS and 59% in OPAL. Updated survival results will be presented. Conclusions: If the association is confirmed in this updated analysis, then increasing vitamin D concentrations may provide a way to improve survival following OvCa. Key messages: Higher circulating vitamin D concentrations may improve survival in OvCa.